Comparison of Provisional Crown Materials In Terms of Microhardness - Nik Alyana Syakirin; Nina Djustiana; Zulia Hasratiningsih (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2012)
Recently, composite resin has been a material option on making provisional crown besides acrylic resin, while waiting for the definitive crown restoration to finish for the next treatment. The purpose of this study was to compare the microhardness between two materials of provisional crown materials that are available in the market, composite resin and acrylic resin. The method used for this study is experimental laboratory. Five samples each from composite resin and acrylic resin were made in disc shape sizes of 6x4mm. The samples were put in artificial saliva with mouth temperature of 37o for 24 hours and tested later using Vickers Hardness tester. Results show the average of microhardness acrylic resin was 9.14 VHN and 10.69 VHN for composite resin. Even though on average number composite resin was higher by 1.55 VHN than acrylic resin, t-test statistics shows there is no significant difference between composite resin and acrylic resin. The conclusion of the research is there is no significant difference between provisional crown composite resin and provisional crown acrylic resin, although on average composite resin has higher hardness number than acrylic resin.